IMPROVING STUDENT (SANTRI) CARE FOR THE LIVING ENVIRONMENT IN NURUL HUDA ISLAMIC BOARDING SCHOOL, DEPOK - Sri Rahayu Pudjiastuti (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2020)
In general, santri (student) in islamic boarding school do not have clean habits. The habit that is actually throwing garbage in the river/sewer, someone else's yard, empty land, by burning it, or handing over garbage that has not been sorted out to the garbage officer/cleaning service. This study aims to provide an overview, analysis and recommendations (problem solving) about the need to strengthen environmental education (specifically about waste) to increase santri concern for the environment. This research method uses descriptive analysis method that is supported by secondary data and literature studies. The number of respondents 80 santri (santri). The results showed: environmental care programs can be realized well if supported by four basic elements namely; policies of environmentally friendly institutions, implementation of environment-based curriculum, participatory-based environmental activities, and management of environmentally friendly supporting facilities. The environmental care program is essentially the formation of attitudes and behaviors that are pro-environment, including waste management which applies the 3R principle (reuse, reduse, recycle) to reuse goods, reduce consumption on goods, and recycle items that are is not used anymore